Building Customer Loyalty through Service Quality and Satisfaction: A Study at PDAM KCP Sei Agul - Pika Dea Krismalem; Dianty Putri Purba; Rebecca Evadine (Lembaga Riset dan Inovasi Al-Matani, 2025)
This study aims to assess how the variables of Service Quality and Customer Satisfaction influence Customer Loyalty at PDAM KCP Sei Agul. The research method used is a quantitative approach by distributing online questionnaires to 30 respondents who served as the sample for this study. Data were analyzed using SPSS version 25 with a multiple linear regression approach. The results of the study indicate that both Service Quality and Customer Satisfaction variables have a partial effect on Customer Loyalty. However, these variables do not have a simultaneous effect on Customer Loyalty.